Design Methodology for Soft Wearable Devices—The MOSAR Case - Juana-Mariel Dávila-Vilchis; LAZ-Avilés; Juan Carlos Ávila Vilchis; Adriana H. Vilchis-González (Applied Sciences, 2019)
This paper proposes a methodology from the conception to the manufacture of soft wearable devices (SWD). This methodology seeks to unify medical, therapeutic and engineering guidelines for research, development and innovation. The aforementioned methodology is divided into two stages (A and B) and four phases. Stage A only includes phase 1 to identify the main necessity for a patient that will define the target of its associated device. Stage B encompasses phases 2, 3 and 4. The development of three models (virtual, mathematical and experimental physical) of the required device is addressed in phase 2. Phase 3 concerns the control and manufacture of the experimental physical model (EPM). Phase 4 focuses on the EPM experimental validation. As a result of this methodology, 13 mobility, 11 usability and 3 control iterative design criteria for SWD are reported. Moreover, more than 50 products are provided on a technological platform with modular architectures that facilitate SWD diversification. A case study related to a soft mobilizer for upper limb rehabilitation is reported. Nevertheless, this methodology can be implemented in different areas and accelerates the transition from development to innovation.